Implementasi Strategi Pemasaran UMKM Tri.Crochet Situgede untuk Meningkatkan Penjualan Produk Rajutan Tangan (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service article aims to improve the marketing capacity of UMKM Tri.Crochet Situgede through the implementation of an integrated digital marketing strategy. The method used is qualitative with a Participatory Action Research (PAR) approach, involving collaboration between the implementation team and the UMKM owners. The program includes need assessment, branding improvement, promotional content creation, product photography, and optimization of Instagram and TikTok as the primary marketing platforms. Training and technical assistance were provided to enable UMKM to independently create content, manage posting schedules, and expand promotional reach. The results show a significant improvement in visual content quality, audience engagement, account reach, and product visibility. This directly impacted the increase in product sales. The findings indicate that an effective digital marketing strategy can enhance the competitiveness and market penetration of creative UMKM. Ongoing mentoring also proved crucial in ensuring the sustainability of marketing practices applied to handmade craft UMKM, allowing them to continue growing in an increasingly competitive market.